Pengaruh Firm Size, Financial Leverage, dan Institutional Ownership pada Praktik Income Smoothing - Junianto, Adhitiya; Wisadha, I Gede Suparta (E-Jurnal Akuntansi, 2014)
Income smoothing is one form of which profit management conducted by corporate management on earnings that is produced on a certain period. Income smoothing performed with the purpose of reducing the level of fluctuations of profit generated between a period so that the financial condition of the company would be visible stable and risky low. Income smoothing can result in the content of information in a financial statements become less accurately. The goal of this research was to test whether there is influence of firm size, financial leverage, and institutional ownership in income smoothing practice. Sector f&b companies listed on the Indonesia S tock E xchange during the period 2009 until 2011 set as population research. For sample research, selected by as much as 14 companies that are set up as a sample number of observations so that total with a three-year research period is as much as 42 observation. Logistic regression was used as the data analysis techniques in this research. Based on data analysis techniques, namely a logistic regression was done in this research , the results of the research had finally been obtained. Firm size and financial leverage gives a positive influence on the income smoothing practice, while institutional ownership gives a negative influence.
Keywords: income smoothing, firm size, financial leverage, institutional ownership